2018
DOI: 10.1002/jmr.2736
|View full text |Cite
|
Sign up to set email alerts
|

Quantum mechanical studies on dioxin‐imprinted polymer precursor composites: Fundamental insights to enhance the binding strength and selectivity of biomarkers

Abstract: We present a benchmark study of binding energies for dioxin-imprinted polymer complexes. A density functional theory approach was used for screening the polymerization precursors in the rational design of molecularly imprinted polymers (MIPs). Tetrachlorodibenzo-p-dioxin (TCDD) was taken as an imprinted molecule. The geometry optimization, natural bond orbital charge, and molecular electrostatic potential of TCDD and acrylamide (AM) were studied at the M062X level and 6-31G(d,p) belonging to one of the hybrid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…The polymer matrix is an artificial synthetic polymer matrix that possesses specific cavities and recognition sites and binds specifically with the target molecule . Molecularly imprinted polymers (MIPs) are easily prepared, stable, and cheap, and these materials are produced in large quantities with good reusability; they have been used in many different areas such as biological molecules and analytical applications . Studies in recent years have shown that MIPs have received considerable scientific attention in the field of sensors .…”
Section: Introductionmentioning
confidence: 99%
“…The polymer matrix is an artificial synthetic polymer matrix that possesses specific cavities and recognition sites and binds specifically with the target molecule . Molecularly imprinted polymers (MIPs) are easily prepared, stable, and cheap, and these materials are produced in large quantities with good reusability; they have been used in many different areas such as biological molecules and analytical applications . Studies in recent years have shown that MIPs have received considerable scientific attention in the field of sensors .…”
Section: Introductionmentioning
confidence: 99%
“…These functionals also yield good results for systems containing dispersion forces [ 77 , 78 , 79 , 80 ]. To select the appropriate DFT method, Khan et al [ 81 ] used several methods—B3LYP, BHandHLYP, M062X, and ωB97xD—and basis sets—6-31G(d,p) and 6-31++G(d,p)—to optimize of the template structure. They analyzed and compared the optimized results with earlier experimental data available in the literature.…”
Section: Quantum Mechanics Methods To Design Mipsmentioning
confidence: 99%
“…One also may realize that MDPV's tertiary amine is rather hindered while the MDPV molecule interacts with an o-PD shell-a key conclusion driven by Monte Carlo sampling-to be able to contribute to the cavities' selectivity. To evaluate the distribution of non-covalent interactions between o-PD monomers and MDPV in the MIP pre-polymerization complexes, analysis of Becke surface [113] was performed for the pre-polymerization cavities with higher representativity, i.e., the complexes with 19, 20 and 21 monomers. This analysis was based on Hirshfeld surface [114], applying the Becke's [115], instead of the Hirschfeld's, partition.…”
Section: Theoretical Studiesmentioning
confidence: 99%